1989
DOI: 10.1111/j.1432-1033.1989.tb15033.x
|View full text |Cite
|
Sign up to set email alerts
|

Conformational consequences of the incorporation of arabinofuranosylcytidine in DNA

Abstract: The self-complementary octamers d(CGCTAGCG) and d(CGaCTAGCG) (aC, arabinofuranosylcytidine) were studied by means of NMR spectroscopy. It is shown that d(CGaCTAGCG), under suitable conditions of oligonucleotide concentration, ionic strength and temperature, exclusively adopts a hairpin structure. However, under the same experimental conditions (5 mM DNA, no added salt, 295 K) d(CCCTAGCG) mainly adopts a B-DNA-type duplex. At lower temperatures (G290 K) the hairpin form of d(CGaCTACCG) occurs in slow exchange w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In addition, the C2-OH of the arabinose sugar was seen to project into the major groove of the helix at a site that is normally quite hydrophobic. NMR studies (Pieters et al, 1989(Pieters et al, ,1990Schweitzer et al, 1994) are largely consistent with the crystallographic study but reached different conclusions about the arabinose sugar conformation.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, the C2-OH of the arabinose sugar was seen to project into the major groove of the helix at a site that is normally quite hydrophobic. NMR studies (Pieters et al, 1989(Pieters et al, ,1990Schweitzer et al, 1994) are largely consistent with the crystallographic study but reached different conclusions about the arabinose sugar conformation.…”
Section: Discussionmentioning
confidence: 68%
“…Previous Cytarabine Studies. The importance of cytarabine for the treatment of leukemia has resulted in a number of investigations aimed at detecting structural alterations in nucleic acids substituted with cytarabine ( ). Monomeric cytarabine adopts a C2‘-endo sugar pucker in the crystalline state, the same sugar pucker adopted by aC20 of [ARAC] in the present investigation ().…”
Section: Discussionmentioning
confidence: 99%
“…In an early study, a coupling constant analysis by solution NMR on the araC mononucleoside demonstrated that the araC sugar adopted a conformation under neutral pH conditions that was 50% C2'-endo and 50% C3'-endo, similar to that for ribocytosine; furthermore, no evidence for the type of intramolecular hydrogen bonding observed in the X-ray structure of the mononucleoside was seen under neutral conditions in solution (Remin et al, 1976). Two more recent NMR studies have been carried out on the decamer [d(CG) (araC)d(TAGCG)] 2 (Pieters et al, 1989(Pieters et al, ,1990). In the first report, incorporation of araC was found to promote increased formation of a hairpin structure in which the central TA residues formed the loop of the hairpin (Pieters et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Two more recent NMR studies have been carried out on the decamer [d(CG) (araC)d(TAGCG)] 2 (Pieters et al, 1989(Pieters et al, ,1990). In the first report, incorporation of araC was found to promote increased formation of a hairpin structure in which the central TA residues formed the loop of the hairpin (Pieters et al, 1989). Some formation of the duplex was observed, however, and a qualitative analysis of the data indicated that this duplex was B-type in structure.…”
Section: Discussionmentioning
confidence: 99%